2022
DOI: 10.3390/jcm11030676
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic Features and Morphology of Endobronchial Tuberculosis: A Malaysian Tertiary Hospital Experience

Abstract: The diagnosis of endobronchial tuberculosis (EBTB) is difficult as it is not well visualized radiologically, and bronchoscopy is not routinely performed for tuberculosis (TB) patients. Bronchoscopic characterization via endoscopic macroscopic features can speed up the diagnosis of EBTB and prompt immediate treatment. In this study, we identified the clinical and bronchoscopic morphology of 17 patients who were diagnosed with EBTB from 2018 to 2020. Demographics, radiological, microbiological and histopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The median age of patients with EBTB was relatively higher (74 years) than that reported in previous studies (48 years) (21). Regarding bronchoscopic findings, the most common type was the active caseating (54.4%) which was consistent with results from previous studies (12,(21)(22)(23). However, Ozkaya et al reported the most common type as the edematous hyperaemic subtype (24).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The median age of patients with EBTB was relatively higher (74 years) than that reported in previous studies (48 years) (21). Regarding bronchoscopic findings, the most common type was the active caseating (54.4%) which was consistent with results from previous studies (12,(21)(22)(23). However, Ozkaya et al reported the most common type as the edematous hyperaemic subtype (24).…”
Section: Discussionsupporting
confidence: 85%
“…Although EBTB was known to have a predilection for young women previously, this study showed that EBTB occurred commonly in elderly patients (16,22). In South Korea, TB was a major infectious disease in the 1940s, and its incidence was high until 2016 (2,27).…”
Section: Discussionmentioning
confidence: 68%